2022
DOI: 10.3390/diagnostics12051065
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Antigen: Clinical Application and Research Status

Abstract: The squamous cell carcinoma antigen (SCCA) is a tumor marker that has gained increasing attention for its biological functions and significance in normal physiological and pathological processes. Not only SCCA but also circulating immune complexes of SCCA and immunoglobulin M (IgM) are involved in normal physiological and pathological processes, providing a background for numerous clinical studies aimed at assessing the potential role of SCCA, SCCA–IgM, and SCCA isoform complexes in clinical practice. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 92 publications
1
22
0
1
Order By: Relevance
“…But gender differences have to be considered, as low levels of SCCA-IgM after transarterial embolization indicate more prolonged survival in males and shorter in females ( 213 ). SCCA and SCCA-IgM show moderate diagnostic accuracy in several meta-analyses ( 214 216 ). Combination with AFP increases prognostic value significantly ( 214 ).…”
Section: Promising New Biomarkers For Clinical Applicationmentioning
confidence: 99%
“…But gender differences have to be considered, as low levels of SCCA-IgM after transarterial embolization indicate more prolonged survival in males and shorter in females ( 213 ). SCCA and SCCA-IgM show moderate diagnostic accuracy in several meta-analyses ( 214 216 ). Combination with AFP increases prognostic value significantly ( 214 ).…”
Section: Promising New Biomarkers For Clinical Applicationmentioning
confidence: 99%
“…SCCA, also known as squamous cell carcinoma antigen, has emerged as a prominent tumor marker. It has garnered significant attention because of its multifaceted biological functions and profound implications in both normal physiological processes and pathological conditions [9]. Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hematological but not in ammatory indicator SCC-Ag shows the independent predictive value for DFS. This may be because, on the one hand, SCC-Ag is associated with the expression of E-cadherin and β-catenin, which trigger epithelial-mesenchymal transition and promote invasion and metastasis; on the other hand, SCC-Ag secreted by tumor cells in lymph nodes and circulating tumor cells is also more easily detected in the blood stream [27]. Moreover, by further calculating the cut-off value, we found that cervical cancer patients with SCC-Ag < 1.47ng/ml had a lower risk of recurrence and metastasis, similar to the results of Salvatici[28], which may have some reference value for further clinical strati cation.…”
Section: Discussionmentioning
confidence: 99%